Microbiologic, Pharmacokinetic, and Clinical Effects of Corneal Collagen Cross-Linking on Experimentally Induced Pseudomonas Keratitis in Rabbits. Issue 10 (October 2015) - Cosar, C. Banu; Kucuk, Mutlu; Celik, Ekrem; Gonen, Tansu; Akyar, Isin; Serteser, Mustafa; Tokat, Fatma; Ince, Umit
Abstract : Purpose: To determine the effects of corneal collagen cross-linking (CXL) on the penetration of topical 0.5% moxifloxacin, on the number of colony-forming units (CFUs) in the cornea, and on the clinical course in a rabbit eye model of experimentally induced Pseudomonas aeruginosa keratitis. Methods: In this prospective animal study, experimental Pseudomonas corneal ulcers were induced in 56 corneas of 28 albino New Zealand rabbits. The corneas were randomly divided into the following 4 groups: the control group (14 eyes), the MOX group (moxifloxacin) (14 eyes), the MOX + CXL group (14 eyes), and the CXL group (14 eyes). On day 4 of the experiment, the eyes in the control group were enucleated and CFU counting was performed. On day 10 of the experiment, all eyes were enucleated and CFU counting was performed. In the MOX and MOX + CXL groups, the moxifloxacin level in the cornea, aqueous humor, iris, plasma, and serum was measured by reverse-phase high-performance liquid chromatography. Results: The difference in the corneal CFU count between the MOX group and the MOX + CXL group was not significant ( P = 0.317). Clinical improvement was greatest in the MOX + CXL group ( P < 0.001). The mean corneal moxifloxacin level was 0.391 ± 0.09 μg·mg −1 in the MOX group versus 0.291 ± 0.09 μg·mg −1 in the MOX + CXL group; as such, CXL did not have a significant effect on antibiotic penetrance ( P = 0.386). Conclusions: Clinical improvement was greatest in the MOX + CXL group. The synergistic effect of CXL on corneal ulcer treatment is not through antibiotic penetrance.